Global, Regional, and National Burden of Calcific Aortic Valve and Degenerative Mitral Valve Diseases, 1990–2017. Issue 21 (26th May 2020) - Yadgir, Simon; Johnson, Catherine Owens; Aboyans, Victor; Adebayo, Oladimeji M.; Adedoyin, Rufus Adesoji; Afarideh, Mohsen; Alahdab, Fares; Alashi, Alaa; Alipour, Vahid; Arabloo, Jalal; Azari, Samad; Barthelemy, Celine M.; et al.
Abstract : Background: Nonrheumatic valvular diseases are common; however, no studies have estimated their global or national burden. As part of the Global Burden of Disease Study 2017, mortality, prevalence, and disability-adjusted life-years (DALYs) for calcific aortic valve disease (CAVD), degenerative mitral valve disease, and other nonrheumatic valvular diseases were estimated for 195 countries and territories from 1990 to 2017. Methods: Vital registration data, epidemiologic survey data, and administrative hospital data were used to estimate disease burden using the Global Burden of Disease Study modeling framework, which ensures comparability across locations. Geospatial statistical methods were used to estimate disease for all countries, because data on nonrheumatic valvular diseases are extremely limited for some regions of the world, such as Sub-Saharan Africa and South Asia. Results accounted for estimated level of disease severity as well as the estimated availability of valve repair or replacement procedures. DALYs and other measures of health-related burden were generated for both sexes and each 5-year age group, location, and year from 1990 to 2017. Results: Globally, CAVD and degenerative mitral valve disease caused 102 700 (95% uncertainty interval [UI], 82 700–107 900) and 35 700 (95% UI, 30 500–42 500) deaths, and 12.6 million (95% UI, 11.4 million–13.8 million) and 18.1 million (95% UI, 17.6 million–18.6 million) prevalent cases existed in 2017, respectively. A total of 2.5 million (95% UI, 2.3 million–2.8 million) DALYs were estimated as caused by nonrheumatic valvular diseases globally, representing 0.10% (95% UI, 0.09%–0.11%) of total lost health from all diseases in 2017. The number of DALYs increased for CAVD and degenerative mitral valve disease between 1990 and 2017 by 101% (95% UI, 79%–117%) and 35% (95% UI, 23%–47%), respectively. There is significant geographic variation in the prevalence, mortality rate, and overall burden of these diseases, with highest age-standardized DALY rates of CAVD estimated for high-income countries. Conclusions: These global and national estimates demonstrate that CAVD and degenerative mitral valve disease are important causes of disease burden among older adults. Efforts to clarify modifiable risk factors and improve access to valve interventions are necessary if progress is to be made toward reducing, and eventually eliminating, the burden of these highly treatable diseases. Abstract : Supplemental Digital Content is available in the text.